A systematic review and meta-analysis of thiazide-induced hyponatraemia: time to reconsider electrolyte monitoring regimens after thiazide initiation? - Barber, Jennifer; McKeever, Tricia M.; McDowell, Sarah E.; Clayton, Jennifer A.; Ferner, Robin E.; Gordon, Richard D.; Stowasser, Michael; O'Shaughnessy, Kevin M.; Hall, Ian P.; Glover, Mark (Wiley, 2015)
Aims: Hyponatraemia is one of the major adverse effects of thiazide and thiazide-like diuretics and the leading cause of drug-induced hyponatraemia requiring hospital admission. We sought to review and analyze all published cases of this important condition.